Activation of pregnane X receptor induces atherogenic lipids and PCSK9 by a SREBP2-mediated mechanism - Karpale Mikko; Käräjamäki Aki J; Kummu Outi; Gylling Helena; Hyötyläinen Tuulia; Oresic Matej; Tolonen Ari; Hautajärvi Heidi; Savolainen Markku J; Ala-Korpela Mika; Hukkanen Janne; Hakkola Jukka (WILEY, 2022)
Background and Purpose Many drugs and environmental contaminants induce hypercholesterolemia and promote the risk of atherosclerotic cardiovascular disease. We tested the hypothesis that pregnane X receptor (PXR), a xenobiotic-sensing nuclear receptor, regulates the level of circulating atherogenic lipids in humans and utilized mouse experiments to identify the mechanisms involved.Experimental Approach We performed serum NMR metabolomics in healthy volunteers administered rifampicin, a prototypical human PXR ligand or placebo in a crossover setting. We used high-fat diet fed wild-type and PXR knockout mice to investigate the mechanisms mediating the PXR-induced alterations in cholesterol homeostasis.Key Results Activation of PXR induced cholesterogenesis both in pre-clinical and clinical settings. In human volunteers, rifampicin increased intermediate-density lipoprotein (IDL), low-density lipoprotein (LDL) and total cholesterol and lathosterol-cholesterol ratio, a marker of cholesterol synthesis, suggesting increased cholesterol synthesis. Experiments in mice indicated that PXR activation causes widespread induction of the cholesterol synthesis genes including the rate-limiting Hmgcr and upregulates the intermediates in the Kandutsch-Russell cholesterol synthesis pathway in the liver. Additionally, PXR activation induced plasma proprotein convertase subtilisin/kexin type 9 (PCSK9), a negative regulator of hepatic LDL uptake, in both mice and humans. We propose that these effects were mediated through increased proteolytic activation of sterol regulatory element-binding protein 2 (SREBP2) in response to PXR activation.Conclusion and Implications PXR activation induces cholesterol synthesis, elevating LDL and total cholesterol in humans. The PXR-SREBP2 pathway is a novel regulator of the cholesterol and PCSK9 synthesis and a molecular mechanism for drug- and chemical-induced hypercholesterolemia.